Identifying Patterns Across the Six Canonical Factors Underlying Wrongful Convictions - Berube, Ryanne; Wilford, Miko M.; Redlich, Allison D.; Wang, Yan (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2022)
Research has established six “canonical” factors underlying wrongful convictions including: mistaken witness identification (MWID), false confession (FC), perjury or false accusation (P/FA), false or misleading forensic evidence (F/MFE), official misconduct (OM), and inadequate legal defense (ILD). While we know these factors do not occur in isolation, researchers have yet to examine the patterns across these six factors. In the present article, we apply latent class analysis to explore how these six factors might co-occur across known exonerations. Using data from the National Registry of Exonerations, we identify four latent classes by which the incidence rates across these six factors can be categorized. Among our noteworthy findings: 1) P/FA and OM often co-occur, 2) when MWIDs are high, the incidence of other factors is relatively low, and 3) false guilty pleas had the highest prevalence in a class that was generally associated with Failures to Investigate. Further implications are discussed.